2020
DOI: 10.1017/s1754470x20000495
|View full text |Cite
|
Sign up to set email alerts
|

Making friends with uncertainty: experiences of developing a transdiagnostic group intervention targeting intolerance of uncertainty in IAPT. Feasibility, acceptability and implications

Abstract: Co-morbid mental health diagnoses present challenges for services structured to provide disorder-specific models of treatment, such as those structured around Improving Access to Psychological Therapies (IAPT). Intolerance of uncertainty (IU) has been identified as both disorder specific and transdiagnostic, although little research explores transdiagnostic approaches to treatment of IU alone. A cognitive behavioural therapy treatment targeting IU previously established for individual therapy was adapted for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…We are referring to uncertainty distress rather than to anxiety (health anxiety or other forms anxiety), stress, worry or burden because although the framework we propose has implications for all of these, the emphasis in this article is on dimensions of uncertainty rather than threat or the broader impact. Although this article is written in the context of Coronavirus, the ideas were based on work developing and testing treatments for the anxiety disorders (Mofrad and Tiplady, 2019; Tiplady et al ., 2017) and further developed with reference to (amongst others) caregivers of dementia, caregivers facing acute and potentially life-threatening paediatric health conditions, caregivers of adults with developmental difficulties, multi-disciplinary teams working with a range of problems under conditions of actual uncertainty, asylum seekers, other people living under conditions of psychosocial instability, long-term health conditions, and so on.…”
Section: Rationalementioning
confidence: 99%
“…We are referring to uncertainty distress rather than to anxiety (health anxiety or other forms anxiety), stress, worry or burden because although the framework we propose has implications for all of these, the emphasis in this article is on dimensions of uncertainty rather than threat or the broader impact. Although this article is written in the context of Coronavirus, the ideas were based on work developing and testing treatments for the anxiety disorders (Mofrad and Tiplady, 2019; Tiplady et al ., 2017) and further developed with reference to (amongst others) caregivers of dementia, caregivers facing acute and potentially life-threatening paediatric health conditions, caregivers of adults with developmental difficulties, multi-disciplinary teams working with a range of problems under conditions of actual uncertainty, asylum seekers, other people living under conditions of psychosocial instability, long-term health conditions, and so on.…”
Section: Rationalementioning
confidence: 99%
“…This then reduces the capacity to endure one's own distress when there is a perceived absence of enough information to make a situation seem safe. Those who have trouble tolerating uncertainty may use the following strategies: (a) over-engagement, such as over-planning, preparation, or prediction; (b) under-engagement, such as avoiding preparing for something or not engaging in activities to reduce uncertainty-related discomfort; and (c) impulsivity, or acting impulsively, which leads to quick and less thought-out choices [122] . Behavioral treatment components related to intolerance of uncertainty aim to (a) teach about the effects of uncertainty and the difference between "uncertain" and "unsafe"; (b) target the "threat" component through cognitive restructuring; (c) increase awareness of preferred responses to uncertainty discomfort; and (d) "stretch" the capacity to experiment with uncertainty in a variety of areas of one's life [122] .…”
Section: Disaster Mental Health-informed Principles For More Intensiv...mentioning
confidence: 99%
“…Those who have trouble tolerating uncertainty may use the following strategies: (a) over-engagement, such as over-planning, preparation, or prediction; (b) under-engagement, such as avoiding preparing for something or not engaging in activities to reduce uncertainty-related discomfort; and (c) impulsivity, or acting impulsively, which leads to quick and less thought-out choices [122] . Behavioral treatment components related to intolerance of uncertainty aim to (a) teach about the effects of uncertainty and the difference between "uncertain" and "unsafe"; (b) target the "threat" component through cognitive restructuring; (c) increase awareness of preferred responses to uncertainty discomfort; and (d) "stretch" the capacity to experiment with uncertainty in a variety of areas of one's life [122] . Experts on this topic are currently developing and testing a model to clarify how actual and perceived threat, actual and perceived uncertainty, and situationspecific tolerance for uncertainty can make unique contributions to variance in uncertainty distress [121].…”
Section: Disaster Mental Health-informed Principles For More Intensiv...mentioning
confidence: 99%
“…anxiety, depression, stress and trauma, and obsessive-compulsive disorders) (McEvoy et al, 2019). Moreover, emerging research demonstrates that high levels of self-reported intolerance of uncertainty can be reduced to some extent through short-term interventions in the general population (Dunsmoor et al, 2015;Li et al, 2021;Morriss et al, 2020;Oglesby et al, 2017;Wake et al, 2021), and longer-term transdiagnostic (Sperling, 2022;Talkovsky & Norton, 2016), general (McEvoy & Erceg-Hurn, 2016;Palitz et al, 2019), and intolerance of uncertainty-specific (Dugas et al, 2022;Hebert & Dugas, 2019;Mofrad et al, 2020) standardised treatment protocols (e.g., cognitive behavioural therapy) in clinical populations. Given this progress, there is an increasing need for research examining the neural and psychophysiological basis of intolerance of uncertainty (Morriss et al, 2021;Tanovic et al, 2018), in order to enhance our mechanistic understanding of how intolerance of uncertainty modulates key processes relevant to the pathogenesis and treatment of emotional disorders (Einstein, 2014;Grupe & Nitschke, 2013;Hong & Cheung, 2015;Paulus et al, 2015;Shihata et al, 2016).…”
Section: Introductionmentioning
confidence: 99%